Critical roles of the miR-17∼92 family in thymocyte development, leukemogenesis, and autoimmunity - Kunyu Liao; Pengda Chen; Mengdi Zhang; Jiazhen Wang; Teri Hatzihristidis; Xiaoxi Lin; Liang Yang; Nan Yao; Chenfeng Liu; Yazhen Hong; Xia Li; Hong Liu; et al. (Cell Reports, 2024)
Summary: Thymocyte development requires precise control of PI3K-Akt signaling to promote proliferation and prevent leukemia and autoimmune disorders. Here, we show that ablating individual clusters of the miR-17∼92 family has a negligible effect on thymocyte development, while deleting the entire family severely impairs thymocyte proliferation and reduces thymic cellularity, phenocopying genetic deletion of Dicer. Mechanistically, miR-17∼92 expression is induced by Myc-mediated pre-T cell receptor (TCR) signaling, and miR-17∼92 promotes thymocyte proliferation by suppressing the translation of Pten. Retroviral expression of miR-17∼92 restores the proliferation and differentiation of Myc-deficient thymocytes. Conversely, partial deletion of the miR-17∼92 family significantly delays Myc-driven leukemogenesis. Intriguingly, thymocyte-specific transgenic miR-17∼92 expression does not cause leukemia or lymphoma but instead aggravates skin inflammation, while ablation of the miR-17∼92 family ameliorates skin inflammation. This study reveals intricate roles of the miR-17∼92 family in balancing thymocyte development, leukemogenesis, and autoimmunity and identifies those microRNAs (miRNAs) as potential therapeutic targets for leukemia and autoimmune diseases.